Азиміна трилопатева (Asimina triloba (L.) Dun.): стан та перспективи культури, біоекологічні особливості в умовах вирощування на півдні України - Grabovetzkaya, O.A.; Derevyanko, V.N.; Khokhlov, S.Yu. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
A state and prospects of culture of new fruit plant – papaw (Asimina triloba (L.) Dun.) are elucidated. The data about biological and ecological features on the south of Ukraine are presented.